Formação continuada de professores em serviço: implicações no processo do desenvolvimento profissional - Fontoura, Marta Regina (2018)
This dissertation, which is part of the research line LP2 Pedagogical Management and Educational Contexts of the Post-Graduate Program in Public Policies and Educational Management, Professional Master's, Federal University of Santa Maria. The objective of this study was to understand the processes of continuing teacher training in the Marieta D'Ambrósio State School of Education in Santa Maria / RS, as well as the aspects that characterize it in planning and implementation. Subsequently to signal parameters in the elaboration of formative processes with a view to the orientation and the accompaniment of the teachers involved. We understand that understanding the ongoing training processes of in-service teachers requires an opportunity to share experiences and knowledge in a collaborative way. To that end, we sought answers to the problem: How did the processes of continuous teacher training in service developed at the school impact on the professional development of teachers? This qualitative study sought to understand how the school organizes the formative processes carried out in the school space; the challenges that the school and teachers face in the realization and implementation of continuing education; that relations can be established between the processes of in-service teacher education and the Pedagogical Political Project, and that actions can make a proposal of school organization based on the demands evidenced in the research. As instruments of information collection were used semi-structured interviews directed to four members of the directive / pedagogical coordination team and eight teachers. The interviews were developed according to the stages of the Bardin Content Analysis, with three categories in the first question: participation in the planning of continuing education in the school; organization of teacher training activities and as provided for in the Pedagogical Political Project; evaluation of teacher involvement in the formative actions organized by the school. For the second question were two categories: challenges faced by the school in carrying out the training actions and strengths and weaknesses of the ongoing training processes you experience in school. In the third question were four categories: conception of continuing education; relations of the formative actions with the expectations of the teachers of the school and what favor the professional development; investment in the continuing formation of teachers in the school and relation of the formative processes with the Political Pedagogical Project. As results, the main intensifiers were found: female teachers in the formative actions of the school; continuing education; exchange between peers and experiences; Listening, dialogue among those involved; orientation and accompaniment of the teachers; social and wage devaluation of teachers and democratic management. Faced with this, it was noticed the need for pedagogical accompaniment and organization of spaces for meetings that favor the exchange, integration and the possibility of the teachers to participate in the organization of school work. These findings allowed the construction of the proposal in the fourth question that corresponds to the product: the organization and implementation of a Continuing Training Program for Teachers in Service, involving the teachers of the Initial Years, through a Working Group and Study.